2011
DOI: 10.1016/j.jmoldx.2011.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Copy Number Gains in 11q13 and 8q34 Are Highly Linked to Prognosis in Cutaneous Malignant Melanoma

Abstract: Relating specific genetic alterations to prognosis may help improve prognostication in melanoma, may identify key oncogenic drivers in cancer, and may assist in developing targeted therapies. Characteristic genetic alterations in melanoma include chromosomal copy number aberrations. We evaluated 97 melanomas (55 metastasizing and 42 nonmetastasizing) after a minimum 5-year follow-up in a case-control study using fluorescence in situ hybridization, targeting commonly altered chromosomal loci in melanoma. Eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 17 publications
3
35
1
3
Order By: Relevance
“…Recently, we identified a subgroup of melanomas with chromosomal copy number gains involving v-myc myelocytomatosis viral oncogene homolog (MYC; alias c-MYC) at 8q24 having reproducible clinical and histological features including aggressive clinical course, occurrence in non-chronically sun damaged skin, amelanotic clinical appearance, histology showing a nodular or primary dermal growth (Figure 1a), epidermal consumption, cells with irregular nuclear contours, coarse chromatin and infrequent association with a nevus. 1,2 Specifically, 90% of the melanomas in our database having 8q24 copy number gains were clinically and histologically amelanotic (Figure 1b). Halaban et al 3 have proposed that a number of dominantly acting oncogenes, including MYC, may have upstream regulatory effects on genes critical to melanin pigment synthesis.…”
mentioning
confidence: 94%
“…Recently, we identified a subgroup of melanomas with chromosomal copy number gains involving v-myc myelocytomatosis viral oncogene homolog (MYC; alias c-MYC) at 8q24 having reproducible clinical and histological features including aggressive clinical course, occurrence in non-chronically sun damaged skin, amelanotic clinical appearance, histology showing a nodular or primary dermal growth (Figure 1a), epidermal consumption, cells with irregular nuclear contours, coarse chromatin and infrequent association with a nevus. 1,2 Specifically, 90% of the melanomas in our database having 8q24 copy number gains were clinically and histologically amelanotic (Figure 1b). Halaban et al 3 have proposed that a number of dominantly acting oncogenes, including MYC, may have upstream regulatory effects on genes critical to melanin pigment synthesis.…”
mentioning
confidence: 94%
“…Как и p16 INK4a , циклин D1 реализует свою активность в ядре клетки, но в противопо-ложность p16 INK4a является протоонкогеном [19]. Неоднократно сообщалось об увеличении числа копий гена, кодирующего данный белок, в клетках меланомы кожи взрослых больных [20,21]; увели-чение содержания этого белка в клетках мелано-мы позволило J. Oba и соавт. отличать ее от невусов [22].…”
Section: Discussionunclassified
“…Other case control studies have shown that melanomas with specific chromosomal copy number aberrations such as those with high levels of gains in 11q13 or 8q24 had a significantly worse prognosis than conventional melanomas without these changes. 19,20 While cases with these specific changes clearly have a very poor prognosis and aggressive disease, only a limited percentage of aggressive tumours are identified. Hence, looking at copy number aberrations alone whether by FISH or CGH is unlikely to be a highly accurate method for prognostication of conventional melanomas.…”
Section: Comparative Genomic Hybridisation and Fluorescence In Situ Hmentioning
confidence: 99%